Influence of gestational history on neural tube defects and Eisenmenger syndrome: associations with intellectual disability and visual impairment in children and adults – a systematic review - Dianasari,; ‘Aissy, Chamelia Rohadatul; Javier, R. Mohamad; Nativity, Gabriela; Ahyandi, Syarif Syamsi; Amiralevi, Siti Hani; Putra Arlond, Faisal Gani; Sari, Khomariyana Purnama; Riandata, Mohammad Reza; Putra, Crysciando Jefryco; Prathama, Christopher Bryant; Thiono, Fellicia Raphaela; et al. (Frontiers in Pediatrics, 2025)
The period between conception and childbirth is known as gestational time. The condition of the baby can be affected by processes involved in pregnancy and delivery. History of diabetes and obesity during pregnancy has been proven to increase the risk of Eisenmenger Syndrome and Neural Tube Defect. Eisenmenger Syndrome is a congenital heart anomaly. Congenital heart disease, leading to circulation problems, includes issues with the iris stromal blood vessels, a characteristic feature of Eisenmenger syndrome. The dilation of iris stromal blood vessels due to this issue may lead to visual impairment/disorders. Additionally, individuals with Down syndrome and other forms of mental disorders suffer from congenital heart diseases. To analyze the influence of gestational history on the occurrence of neural tube defects and Eisenmenger syndrome, accompanied by intellectual disability and visual impairment in children and adults. A systematic review in this study was constructed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique. This approach ensures that all stages and research procedures are systematically followed. A total of 2,327 results were obtained after collecting sources from Google Scholar and articles published between 2018 and 2023 were filtered with defined inclusion and exclusion criteria to ensure appropriate study selection. The classification of the number of Scopus-indexed journals is as follows: the number of Q2 Scopus-indexed journals is 5, with a total of five journals taken and used as references for systematic observational research. Gestational history significantly influences the occurrence of neural tube defects and Eisenmenger syndrome, accompanied by intellectual disability and visual impairment in children and adults.